ANTHROPONOTIC CUTANEOUS LEISHMANIASIS IN THE CITY OF BAM, SOUTHEAST IRAN - A. Nadim; M.R. Aflatoonian (Tehran University of Medical Sciences, 1995)
Due to the high prevalence of anthroponotic cutaneous leishmaniosis (ACL) in Barn city, a survey was carried out to determine epidemiological characteristics of ACL in Barn in 1992. For this purpose, 23 out of the total 51 schools (elementary, junior high and senior high) were randomly selected and 6053 students were examined. The prevalence of acute sores and scars were 2% and 17% respectively. A map of the city was prepared, showing the residence of acute cases seen in schools. 3 parts with higher concentration of cases were selected and house - to - house visits were made, examining all age groups. In 2155 persons examined, the prevalence of acute cases was 3.6% and prevalence of scars 26.9%.